Piel en descontrol: Video musical oficial (2025)
“Piel en descontrol” is the first single released by the independent Bogotá-based band A Medio Camino. The song reflects on the romantic longing for an ex-partner who, perhaps at the time, was not given the affection they truly deserved. It talks about the regret of not appreciating a good relationship when you had it. The music video unfolds within the protagonist’s memories as he sings on stage in a bar. He recalls mainly the good moments he once shared with that person, with occasional flashes of the times when he dismissed or overlooked her slipping into his memory from time to time. The members of the band visually accompany this journey with their performance, but they are surrounded by darkness, symbolizing the state of loneliness of the protagonist. Finally, at the climax of the song, it seems as though the protagonist meets his beloved once again in that same bar, and they share the long-awaited kiss, but it all takes place in his mind